A Quality of Growth Index for Developing Countries : A Proposal - Mlachila, Montfort; Tapsoba, Rene.; Tapsoba, Sampawende (Washington, D.C. : International Monetary Fund, 2014)
This paper proposes a new quality of growth index (QGI) for developing countries. The index encompasses both the intrinsic nature and social dimensions of growth, and is computed for over 90 countries for the period 1990-2011. The approach is premised on the fact that not all growth is created equal in terms of social outcomes, and that it does matter how one reaches from one level of income to another for various theoretical and empirical reasons. The paper finds that the quality of growth has been improving in the vast majority of developing countries over the past two decades, although the rate of convergence is relatively slow. At the same time, there are considerable cross-country variations across income levels and regions. Finally, emprirical investigations point to the fact that main factors of the quality of growth are political stability, public pro-poor spending, macroeconomic stability, financial development, institutional quality and external factors such as FDI.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet